KAJIAN PELUANG INVESTASI PABRIKASI KECAP DI KABUPATEN PURBALINGGA TAHUN 2008 - Refius Pradipta S (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2008)
The aim of this research is to analyze suitable natural phosphate manure production in Sawangan Ajibarang phosphate factory. The analysis’ tool that used is five aspects they are Market aspect, Production and Technology aspect, Management aspect, Financial Aspect and Environment aspect. The market aspect used SWOT analyzes. The management aspect used organizational structure. The Financial aspect used Break Even Point (BEP), Payback Period (PP), Net Present Value (NPV), Profitabilitas Indeks (PI), and Internal Rate of Return (IRR). The result of this research shown that Sawangan Ajibarang phosphate factory was suitable.